Good teaching practices: Re-examining curricula, materials, activities, assessments - KC Lee; Jenny Scoles (University of Johannesburg, 2020)
Issue 4.2 presents 11 full articles, two reflections, and three book reviews from a diverse teaching and learning contexts in terms of discipline, dynamics of students and classroom, region, approach, and so on from Afghanistan, Kenya, New Zealand, Rwanda, Singapore, South Africa, Zambia, Pakistan, United Kingdom, Uganda, and United States.  Separately yet together, these publications provide a timely reminder to us to re-examine what we are doing in our classroom beyond and despite the COVID-19 pandemic.  They surface issues that affect student experience and success such as accessibility, equality, diversity, fairness â€" all of which are what Leibowitz identifies as issues confronting the global South (2017). Keywords: Good teaching practices, global South, SoTL, Scholarship of teaching and learning, Editorial How to cite this article: Lee, K.C. & Scoles, J. 2020. Good teaching practices: Re-examining curricula, materials, activities, assessments. Scholarship of Teaching and Learning in the South. 4(2): 1-5. https://doi.org/10.36615/sotls.v4i2.152. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/